2009
DOI: 10.1007/s11912-009-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Current management of anal canal cancer

Abstract: Squamous cell carcinoma of the anal canal historically has been treated with abdominoperineal resection, resulting in high rates of morbidity and local recurrence. Pioneering work led to the finding that radiation therapy (RT) combined with 5-fluorouracil (5-FU) and mitomycin results in high rates of local control and disease-free and colostomy-free survival without surgery. Prospective randomized trials from Europe and the United States have shown the superiority of RT, 5-FU, and mitomycin over 1) RT alone, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…A recent multi-institutional study by Kachnic et al [19] reported excellent outcomes with low toxicity in the context of anal cancer treatment with dose intensity-modulated radiation therapy. Other radiation therapy approaches with promising outcomes described in the past included 3-dimensional conformational radiotherapy treatment piloted in a phase II study [20], intensity-modulated radiation therapy [21] and sequential intensity-modulated radiation therapy in a combined chemoradiological approach [22]. Improvements in radiation treatments in combination with optimization of chemotherapy may result in reduced toxicities, better outcomes and superior quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A recent multi-institutional study by Kachnic et al [19] reported excellent outcomes with low toxicity in the context of anal cancer treatment with dose intensity-modulated radiation therapy. Other radiation therapy approaches with promising outcomes described in the past included 3-dimensional conformational radiotherapy treatment piloted in a phase II study [20], intensity-modulated radiation therapy [21] and sequential intensity-modulated radiation therapy in a combined chemoradiological approach [22]. Improvements in radiation treatments in combination with optimization of chemotherapy may result in reduced toxicities, better outcomes and superior quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Mitomycin is associated with a 60% incidence of serious (grade 3-4) hematologic, pulmonary, renal toxic events and also hemolytic-uremic syndrome. 33 Cisplatin has also been used in anal canal SCC chemoradiotherapy regimes producing less toxicity than mitomycin with reasonable response rates. The first high-level evidence study, RTOG 98-11, found a higher rate of colostomy formation in the cisplatin group (19% vs 10%) compared with the mitomycin group, suggesting response rates may not be as good.…”
Section: Chemoradiation Treatment Of Anal Canal Squamous Cell Carcinomamentioning
confidence: 99%
“…Although mostly replaced by drugs with higher response rate and less toxicity, it still plays a role in curative treatment of anal cancer in combination with 5-flurouracil and radiation therapy and is also used in palliative chemotherapy [2,3]. The wide clinical anti-cancer effect in combination with specific properties such as non-cell cycle specific and direct cytotoxic effect has also rendered MMC an attractive drug for use by topical administration, utilized in the treatment of as diverse malignancies as bladder cancer and certain tumors of the eye [4,5].…”
Section: Introductionmentioning
confidence: 99%